BRIDGING THE GENDER GAP: WOMEN'S IMPACT IN SOCIAL ENTREPRENEURSHIP - Редько, Катерина (SWorldJournal, 2024)
This article explores the significant role of women in social entrepreneurship and their impact on narrowing the gender gap within this dynamic sector. It delves into the challenges faced by women social entrepreneurs and examines the strategies employed